2020
DOI: 10.31557/apjcp.2020.21.6.1521
|View full text |Cite
|
Sign up to set email alerts
|

Do Subjective Norms Predict the Screening of Cancer Patients’ First-Degree Relatives? A Systematic Review and Meta-Analysis

Abstract: Background: Early detection and preventive measures can reduce the risk of cancer among first degree relatives (FDRs) of cancer patients.Several studies investigated the effect of subjective norm in relation to FDRs’ tendency to conduct preventive behaviors. Therefore, the purpose of this study was to systematically evaluate the effect of subjective norms on cancer patients’ FDRs as well as their willingness for screening. Methods: PubMed and Scopus were studied to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Subjective norms refer to an individual’s perception of social pressures to adopt a specific behavior [ 14 ]. Interestingly, a recent systematic review and meta-analysis examined whether subjective norms predict screening of cancer patients’ first-degree relatives [ 40 ]. Investigators found that recommendation from a physician, healthcare provider, or family/friend significantly increased the likelihood of referring for screening and/or preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…Subjective norms refer to an individual’s perception of social pressures to adopt a specific behavior [ 14 ]. Interestingly, a recent systematic review and meta-analysis examined whether subjective norms predict screening of cancer patients’ first-degree relatives [ 40 ]. Investigators found that recommendation from a physician, healthcare provider, or family/friend significantly increased the likelihood of referring for screening and/or preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, numerous studies in both developed and developing countries documented that greater social support promotes breast cancer screening adherence (Smalls et al, 2018;Documet et al, 2015;Leyva et al, 2015;Donnelly et al, 2013;Ma et al, 2012). Additionally, a systematic review and meta-analysis indicate that injunctive norms (i.e., physician recommendation, and family and friends recommendation) increased the motivation to undergo cancer screening among cancer patients' first-degree relatives (Fattahi Ardakani et al, 2020).…”
Section: Socioemotional Variablesmentioning
confidence: 99%